Analisis Total Quality Management (TQM) dalam Manajemen Pendidikan Tinggi terhadap Peningkatan Mutu Pendidikan Indonesia - Hendrian, Hendrian; Suparno (Indo-MathEdu Intellectuals Journal, 2024)
Higher education in Indonesia faces challenges in improving its quality, especially in the post-COVID-19 era and the development of Artificial Intelligence (AI) technology. This study aims to analyze the implementation of Total Quality Management (TQM) in higher education management and its impact on improving the quality of education in Indonesia. Through a qualitative approach, this study identifies the urgency of higher education management as a determining factor in improving the quality of education and analyzes the development of TQM principles in the context of higher education. Data collection is carried out through relevant literature sourced from google scholar. Data analysis is carried out qualitatively consisting of data reduction, data presentation, and conclusion drawing. The results of data analysis show that higher education management plays a crucial role in the preparation of a quality workforce and TQM can improve the quality of education services. Factors supporting TQM implementation involve good governance, while inhibiting factors involve bureaucratic constraints and lack of efficiency of public services. Thus, the implementation of TQM needs to pay attention to these aspects to achieve a more substantial improvement in the quality of higher education